2020
DOI: 10.1029/2019je006092
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Ionospheric Peak Altitude at Mars in Response to Dust Storms: 13 Years of Observations From the Mars Express Radar Sounder

Abstract: Previous observations have shown that, during Martian dust storms, the peak of the ionosphere rises in altitude. Observational studies of this type, however, have been extremely limited. Using 13 years of ionospheric peak altitude data from the Mars Advanced Radar for Subsurface and Ionosphere Sounding instrument on Mars Express, we study how the peak altitude responded to dust storms during six different Mars years (MY). The peak altitude increased ∼10-15 km during all six events, which include a local dust s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 67 publications
(204 reference statements)
6
33
0
Order By: Relevance
“…We find that the peak densities, once corrected for the SZA, solar radiation output and seasonal variations, are larger over the crustal field regions, confirming previous results obtained with much smaller datasets (Nielsen et al, 2007) 6. The global dust storm in MY28 raised the altitude of the ionospheric peak by about 10-15 km, in agreement with a previous independent analysis of the MARSIS AIS data set (Girazian et al, 2020), with studies of the ionosphere during the MY34 dust storm (Felici et al, 2020), and with modeling results (Fang et al, 2020) Data Availability Statement MARSIS and MaRS data are available in the ESA PSA archive (ftp://psa.esac.esa.int/pub/mirror/MARS-EX-PRESS/MARSIS/ and ftp://psa.esac.esa.int/pub/mirror/MARS-EXPRESS/MRS/). All the data used in this study, including also derived magnitudes, have been made publicly available at Zenodo (https://doi.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find that the peak densities, once corrected for the SZA, solar radiation output and seasonal variations, are larger over the crustal field regions, confirming previous results obtained with much smaller datasets (Nielsen et al, 2007) 6. The global dust storm in MY28 raised the altitude of the ionospheric peak by about 10-15 km, in agreement with a previous independent analysis of the MARSIS AIS data set (Girazian et al, 2020), with studies of the ionosphere during the MY34 dust storm (Felici et al, 2020), and with modeling results (Fang et al, 2020) Data Availability Statement MARSIS and MaRS data are available in the ESA PSA archive (ftp://psa.esac.esa.int/pub/mirror/MARS-EX-PRESS/MARSIS/ and ftp://psa.esac.esa.int/pub/mirror/MARS-EXPRESS/MRS/). All the data used in this study, including also derived magnitudes, have been made publicly available at Zenodo (https://doi.…”
Section: Discussionsupporting
confidence: 91%
“…While the data set used is the same in both studies, different methods are used to examine the effects of the storm. In particular, while we use the SZA-corrected peak altitudes, Girazian et al (2020) use the measured values without any further correction. The fact of obtaining similar results when using different methods gives confidence on the robustness of both analyses.…”
Section: Effects Of the My28 Global Dust Stormmentioning
confidence: 99%
“…Streeter et al, ); 2. a major component of the atmospheric interannual, seasonal, daily, and diurnal variability (see Kleinböhl et al, , for an example related to the diurnal variability); 3. a way to redistribute dust on the planet via long‐range particle transport (as inferred, for instance, using albedo changes: Szwast et al, ); 4. a means of producing perturbations of temperature and density, which propagate from the lower to the upper atmosphere, including the lower thermosphere, the ionosphere, and the magnetosphere (e.g. Girazian et al, ; Xiaohua et al, ); 5. a cause of increased loss of chemical species via escape (e.g. Fedorova et al, ; Heavens et al, ; Xiaohua et al, ); and 6. a source of hazards for spacecraft entry, descent, and landing maneuvers, for operations by solar‐powered surface assets, and for future robotic and human exploration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using 13 years’ observations made by the Mars Advanced Radar for Subsurface and Ionospheric Sounding onboard MEX, Girazian et al. (2020) also found that the peak altitude increased by 10 − 15 km during dust storms over six MYs. As demonstrated by the photochemical equilibrium model of Wang and Nielsen (2003), the elevation in peak ionospheric altitude is mainly attributed to the expansion of the neutral atmosphere during dust storms.…”
Section: Introductionmentioning
confidence: 99%